Analysis Of Online Purchase Decisions With Modeling Structural Equation Based On Variance - Sonny Indrajaya; Melati Pangestu (Jurnal Manajemen, 2022)
The purpose of this study is to be able to test what can influence online purchasing decisions at PT. Go Online Goals. The independent variables obtained from the preliminary survey results are Promotion, Perception of Prices, and Image for Brands. The dependent variable is the decision on the purchase. This research method for analysis uses data as well as variance-based Structural Equations using the Partial Least Square (PLS) tool. The population is residents who live in the DKI Jakarta area with a sample size of 200 respondents. The sampling technique uses convenience sampling. By using a quantitative descriptive approach. The results showed that promotion had a positive and significant effect on purchasing decisions, the perceived price also had a significant positive effect on purchasing decisions, and for the brand image, there was a positive and significant effect on purchasing decisions.